ANALISIS TAHAP PENGELOLAAN KEUANGAN PADA FITUR BANK DIGITAL PT BANK JAGO TBK - Linda Komala (2023)
Bank Jago has a different perspective in offering its financial services, one of which is by providing a flagship feature called Jago Pocket with two main purposes, namely expenditure or savings, which can support customers in managing their finances effectively. The aim of this final project is to understand the features offered by Bank Jago, to know the strategies employed by Bank Jago in supporting financial health, and to understand the implementation of financial management through Bank Jago. The descriptive method was used with two data collection methods, namely library research and documentation method, followed by data analysis techniques using the Bank Jago application and Microsoft Excel. The goal was to systematically describe the analysis of the financial management stages in the digital banking features of PT Bank Jago, Tbk. The analysis results show that the features provided by the Bank Jago application to its customers are flexible, easy to understand, and comprehensive. The strategies employed by Bank Jago to support financial health are appropriate, and the implementation of financial management using the Bank Jago application can assist users through the utilization of the Payment Pocket and Saving Pocket features, which have two modes: autosave mode and non-autosave mode. With these features, Bank Jago hopes to encourage users of the Bank Jago application to be disciplined and consistent in saving to achieve their financial goals according to their needs.